Criminal Sanctions and Legal Protection of Victims against the Crime of Fornication of Minors - Siregar, Rospita Adelina; Frichia Saragih; Petrus Irwan Panjaitan; Yuni Artha Manalu (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2023)
Some of the events are quite an impact on the victim is a felony obscenity. However, this is not a necessarily rule out the existence of criminal acts committed by children. So it’s necessary to apply a legal sanctions and special protection in cases involving these children. As this research highlight the implementation of legal sanctions on minors in cases that will be raised related to fornication by children with Verdict Number 2/ Pid.Sus.Anak/ 2018/ PN PMS. This research is an empirical sociological study, which collects field data for further analysis of the data with the applicable legal rules. The result of this research is the practice of legal sanctions on subject of minors through Verdict Number 2/ Pid.Sus.Anak/ 2018/ PN PMS to a children regarding the sentence of 1 (one) year incarcerated and 3 (three) months of job training has been in accordance with applicable legal rules. Caused the subject is a minor, a child who is 15 (fifteen) years old, based on Law Number 11 of 2012 on The Criminal Justice System of Children, legal protection for minors of victims has been carried out such as legal assistance, psychological assistance, and ensuring that the child still get them rights as a child in society such as receiving education, socializing, and so on, the right not to be covered by the media, in collaboration with the Indonesian Child Protection Commission (“KPAI”) in terms of the victim’s psychology and social issues of the victim.